KRITIK SANAD - Subhan, Suhuf (Al-MAJAALIS, 2013)
Criticism  is  part  of  the  science  sanad  mustholah  very  important hadith,  which  includes  being  able  to  determine  whether  or  not  a  hadith shohih.  This  science  evolved  since  the  days  of  the  prophet  companions, much  more  in  the  time  of  Caliph  Uthman  ibn  Affan  after  the  libel Abdullah Ibn Saba  in the  recent  past  to  his  caliphs. Criterion  validity  isnaad  we  can  see  from  the  definition  itself shohih  the  hadith:  hadith  isnaad  concatenated  (to  the  Prophet  of Sallallahu  'alaihi  wa  sallam)  through  the  narrators  are  fair  and  dhobit  to the  end  without  any  sanad  syudzudz  (irregularities  in  matn)  and  gods (defects).